Das linhas às entrelinhas: a representação das mulheres nas doutrinas penais na segunda metade do século XX nos crimes contra os costumes. - Barbosa, Iricherlly Dayane da Costa (2021)
This work aimed to analyse the ways women were portrayed in criminal legal doctrine, during the second half of the 20th century, when debated the so-called crimes against customs. The hypothesis put forward was that the manuals of Criminal Law depicted women in opposing categories to select those who would be considered truly worthy of the State’s legal protection. Working through the theoretical lenses of black feminism, feminist criminology and critical criminology, it was possible to assess the influence of structural patriarchy and structural racism in the formation of criminal legal thinking, and their reflection upon the Criminal Justice System. The research was divided in two fronts of analyses guided by a historiographic perspective. On the first front, the criminal law manuals, the central historical sources, were studied to find what the text brought up about the portrayal of women. It became noticeable that those authors, ingrained in their chauvinistic views, worked to establish a distinction between two types of women: honest and dishonest ones, the former being the deserving of legal protection. On the second front, the focus was to study what was being said between the lines of those legal textbooks so it would be possible to comprehend more clearly who were the women they were talking about. Therefore, the historical sources previously examined were confronted with the bibliographic references so that a more in-depth study of those determined categories became possible. From this dialogue it was possible to comprehend the decisive manner in which racisms establishes parameters for supposedly undetermined theoretical concepts used by authors in their writings. Thus, connections are made between the socially constructed idea of protected and unprotect women being, respectively, white and black women.